2020
DOI: 10.1111/1462-2920.14990
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐model assessment of hydrological and environmental impacts on streambed microbes in Mediterranean catchments

Abstract: Summary Microbes inhabiting intermittent streambeds are responsible for controlling and developing many biogeochemical processes essential for the ecosystem functions. Although streambed microbiota is adapted to intermittency the intensification of water scarcity and prolonged dry periods may jeopardise their capacity to cope with hydrological changes. This study aims to evaluate whether, and to what extent, the duration of dry periods affects streambed microbial density, diversity, composition (16S rRNA gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 75 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…Specifically, the carbon metabolic activity of the biofilm stabilized at the control level at the end of rewetting after the short-term drought, while it did not return to the control level after the long-term drought (Figure d,g). This result suggested that prolonged drought slowed the recovery rate of the biofilm carbon metabolism, leading to irreversible effects after rewetting. …”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the carbon metabolic activity of the biofilm stabilized at the control level at the end of rewetting after the short-term drought, while it did not return to the control level after the long-term drought (Figure d,g). This result suggested that prolonged drought slowed the recovery rate of the biofilm carbon metabolism, leading to irreversible effects after rewetting. …”
Section: Resultsmentioning
confidence: 99%
“…Litchman & Klausmeier, 2008), others are difficult to measure or cannot be attributed to a single cell (e.g., exo-enzymatic activity and photosynthetic pigment composition; Gionchetta et al, 2020;Colls et al, 2021).…”
Section: Historical Use Of Trait Terms In Freshwater Researchmentioning
confidence: 99%
“…Second, some microorganisms can acquire genes from other species, for example, by horizontal gene transfer (Abby et al., 2012; Polz et al., 2013), limiting the capacity to relate inherited cell traits to fitness. Third, whereas some functional traits can be measured at the cellular level (e.g., cell size, shape, and cell wall structure; Litchman & Klausmeier, 2008), others are difficult to measure or cannot be attributed to a single cell (e.g., exo‐enzymatic activity and photosynthetic pigment composition; Gionchetta et al., 2020; Colls et al., 2021).…”
Section: Trait Definitions Terms and Limitations: A Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…During these phases, the biological stress caused by desiccation is often exacerbated by the incoming solar radiation and high streambed temperatures (i.e., its environmental severity; Muñoz et al 2018; Colls et al 2019). Longitudinal impacts of nonflowing periods have been well described (Shumilova et al 2019; von Schiller et al 2019), but determining the effects of nonflow duration or frequency has been largely limited to experimental manipulation in the field or using mesocosms (Acuña et al 2015; Muñoz et al 2018; Gionchetta et al 2020, Majdi et al 2020).…”
mentioning
confidence: 99%